2022
DOI: 10.3389/fpsyg.2022.950501
|View full text |Cite
|
Sign up to set email alerts
|

Media Richness and Continuance Intention to Online Learning Platforms: The Mediating Role of Social Presence and the Moderating Role of Need for Cognition

Abstract: Continuance intention to online learning platforms has received increased attention in recent years, and media richness has been found to be an important antecedent influencing user retention. However, there is insufficient research on the mediating and moderating mechanism underlying this relation. The purpose of this article is to investigate (a) the positive association between three dimensions of media richness and user continuance intention, (b) the mediating role of social presence in the relationship be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 55 publications
0
3
0
1
Order By: Relevance
“…To develop survey measures, we adopted existing valid scales wherever possible. Specifically, we adapted measures from Abbad (2021), Wang (2022), and Wu and Chen (2017) to assess college students' intention to use OTPs. The items for perceived usefulness and ease of use were mainly adapted from Abbad (2021), Lee and Lehto (2013), Mohammadi (2015), and Wu and Chen (2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To develop survey measures, we adopted existing valid scales wherever possible. Specifically, we adapted measures from Abbad (2021), Wang (2022), and Wu and Chen (2017) to assess college students' intention to use OTPs. The items for perceived usefulness and ease of use were mainly adapted from Abbad (2021), Lee and Lehto (2013), Mohammadi (2015), and Wu and Chen (2017).…”
Section: Methodsmentioning
confidence: 99%
“…Regarding college students' intention to adopt OTPs, using an information technology acceptance and usage model, specifically the TAM, is appropriate; thus, we employed it in this study (Mohammadi, 2015;Wang, 2022;Wu & Chen, 2017). Apart from the constructs in the TAM, this study considers another factor: social influence.…”
mentioning
confidence: 99%
“…Fitur ini memungkinkan peserta lain bisa lebih memperhatikan mahasiswa mana yang belum menjawab atau ikut serta (Henry & Thorsen, 2021;Jebbour & Mouaid, 2019). Temuan ini memperlihatkan bahwa teknologi mampu mendorong kehadiran sosial dalam kegiatan pembelajaran (Wang, 2022). Kehadiran sosial ditunjukkan dari adanya keaktifan mahasiswa dalam berdiskusi, kenyamanan untuk mengungkapkan pendapat, dan adanya rasa semangat untuk mengikuti kegiatan pembelajaran.…”
Section: Youtubeunclassified
“…For instance,Pan et al (2017) revealed that both RI and SI identities have similar effects on user behavior in social media usage Turk et al (2022). andWang (2022) reported that social presence affects users' continuance intention toward online learning platforms Tha et al (2009). showed that social ties positively and significantly affect CUEL.…”
mentioning
confidence: 99%